The profession of neuropsychology in Spain: results of a national survey. Issue 8 (16th November 2016) - Olabarrieta-Landa, Laiene; Caracuel, Alfonso; Pérez-García, Miguel; Panyavin, Ivan; Morlett-Paredes, Alejandra; Arango-Lasprilla, Juan Carlos
Abstract: Objective : To examine the current status of professional neuropsychology in Spain, with particular focus on the areas of professional training, current work situation, evaluation and diagnostic practice, rehabilitation, teaching, and research.Methods : Three hundred and thirty-nine self-identified professionals in neuropsychology from Spain completed an online survey between July and December of 2013. Respondents had an average age of 35.8 years and 77% were women.Results : Ninety-seven percent of the respondents identified as psychologists; 82% of the sample had a master's degree, and 33% a doctoral degree. The majority (91%) received their neuropsychological training at a graduate level; 88% engaged in neuropsychological evaluation, 59% in rehabilitation, 50% in research, and 40% in teaching. Average number of hours per week dedicated to work in neuropsychology was 29.7, with 28% of the respondents reporting working in hospitals, 17% in not-for-profit rehabilitation centers, 15% in universities, and 14% in private clinics. Clinicians primarily work with individuals with stroke, traumatic brain injury, and dementia. The top perceived barriers to development of neuropsychology in Spain included lack of clinical and academic training opportunities, and negative attitude toward professional collaboration.Conclusions : The field of neuropsychology in Spain is young and rapidly growing. There is a need to regulate professional neuropsychology, improve graduate curricula, enhance existing clinical training, develop professional certification programs, validate and create normative data for existing neuropsychological tests, and create new, culturally relevant instruments.